The elevated systemic cytokine levels in HIV patients are not associated with an elevated pulmonary cytokine environment. (February 2020) - Fernandez-Botran, Rafael; Vega, Andrea Reyes; García, Yasmany; Tirumala, Chanakya Charan; Srisailam, Praneet; Raghuram, Anupama; Peyrani, Paula; Furmanek, Stephen; Tella, Mahder Alem; Ritzhentaler, Jeffrey D.; Roman, Jesse; Ramírez, Julio A.
Highlights: Plasma levels of several cytokines and chemokines were elevated in HIV-seropositive subjects. No significant differences in BALF cytokines of HIV-positive vs. negative subjects. Similar pulmonary cytokine environment in HIV patients and controls. Abstract: Background: HIV-positive patients on anti-retroviral therapy (ART) are at higher risk of developing many non-AIDS related chronic diseases, including chronic obstructive pulmonary disease (COPD), compared to HIV-negative individuals. While the mechanisms are not clear, a persistent pro-inflammatory state appears to be a key contributing factor. The aims of this study were to investigate whether HIV-positive patients without COPD present evidence of potentially predisposing abnormal pulmonary cytokine/chemokine environment and to explore the relationship between pulmonary and systemic cytokine levels. Methods: This study included 39 HIV-seropositive and 34 HIV-seronegative subjects without COPD. All were subjected to outpatient bronchoscopy with bronchoalveolar lavage fluid (BALF) aspiration and blood sample collection. The levels of 21 cytokines and chemokines were measured in plasma and BALF using a bead-based multi-analyte assay. Results: In plasma, HIV-infected patients showed significantly increased circulating levels of pro-inflammatory (TNFα) and Th1-associated cytokines (IL-12p70) as well as several chemokines (CXCL11 and CX3CL1). However, no statistically significant differences were found in the numbers of cells, the concentrations of protein and urea as well as cytokine levels in the BALFs of HIV-positive patients when compared to controls. Correlation analysis indicated a potential modulatory effect of the BMI in HIV-seropositive individuals. Conclusions: While our results are consistent with the existence of a systemic pro-inflammatory state in HIV-infected patients, they did not detect significant differences in cytokine levels and other inflammatory markers in the lungs of HIV-positive individuals when compared to HIV-negative controls.